Cognitive And Linguistic Challenges In Teaching Jurisprudential Texts To Non-Native Arabic Speakers: An Analytical And Applied Study/ العقبات المعرفية واللغوية في تدريس المتون الفقهية لغير الناطقين باللغة العربية: دراسة تحليلية تطبيقية - Abdulrahman Bin Khalid Alsaadi (Ijaz Arabi Journal of Arabic Learning, 2026)
This study examines the linguistic, cognitive, and methodological challenges encountered by non-native Arabic speakers in studying classical jurisprudential texts (fiqh manuals). Adopting an analytical and applied approach, the research seeks to uncover the structural sources of difficulty embedded in the concise nature of fiqh texts, as well as in the prevailing methods of teaching and learning them. The study is grounded in the assumption that these challenges are not merely the result of limited linguistic proficiency, but rather stem from the intrinsic characteristics of the jurisprudential text itself, including extreme brevity, dense terminology, abstraction, and implicit methodological presuppositions. The research employs a descriptive-analytical methodology, supported by an applied analysis of selected passages from Al-Ghāyah wa al-Taqrīb by Abū Shujāʿ. The findings indicate that linguistic challenges arise primarily from sentence compression, semantic shifts between lexical and technical meanings, and school-specific legal terminology. Cognitive challenges are linked to deficiencies in mental visualization of legal cases, the widening cultural and temporal gap between classical contexts and contemporary learners, and difficulties in grasping abstract legal concepts and universal legal maxims. Methodological challenges, on the other hand, are manifested in rigid traditional teaching practices, the absence of supportive visual and organizational tools, and an overemphasis on memorization prior to conceptual understanding. The study concludes by proposing practical remedial approaches aimed at narrowing the gap between jurisprudential texts and non-native learners of Arabic, including restructuring teaching methods, employing logical mapping techniques, and utilizing illustrated legal glossaries to facilitate comprehension and the acquisition of juridical competence.